Evaluación del desempeño de compresores centrífugos en plataformas marinas - Hernández Mora, Israel Eliú (Universidad Autónoma Metropolitana, 2018)
The Campeche bay is the area with the highest oil and associated gas production in Mexico. The gas coming from the production marine platforms installed in this region is received in the gas processing centers; these centers are of strategic importance for the production, processing and transportation of gas, and oil derivate products in Mexico. The key equipment in the gas processing centers are the centrifugal compressors, since they are responsible for the reinjection of the gas in order to maintain the pressure in the oil well, of the gas collection, of the gas processing operations (loading and unloading) and of transport and distribution systems. These machines, like any other, require that their performance be evaluated continuously and that predictive, preventive and corrective maintenance plans be carried out. A useful tool to carry out this task are the performance maps; these maps are often provided by the manufacturer; however, these are generated at workshops pressure and temperature conditions where the manufacturer tests it before selling it, besides, the compressor is operated with a specific composition of natural gas different from that in the site intended for installation. This mean that, when moving it to another region with different pressure and temperature conditions that design conditions, and when operating it with another natural gas composition, the performance of the machine will not be the same, so it would be necessary to update the maps every time these parameters change. Motivated by the previously mentioned, this work proposes a methodology for obtaining the updated performance maps of the Nuovo Pignone brand, 2BCL608/N centrifugal compressors, considering the changes in the natural gas composition, and the change in pressure and suction temperature. With these maps the performance of the same compressors will be evaluated and operation recommendations will be made according to the obtained results; La sonda de Campeche es la zona de mayor producción de petróleo y gas asociado en México. El gas proveniente de las plataformas marinas de producción instaladas en esta zona se recibe en los centros de procesamiento de gas; estos tienen una importancia estratégica para la producción, procesamiento y transporte de gas, y productos derivados del petróleo en México. Los equipos clave en los centros de procesamiento de gas son los compresores centrífugos, ya que son los responsables de la reinyección del gas para mantener la presión en el pozo, de la recolección del gas, de las operaciones de procesamiento del gas (carga y descarga y de los sistemas de transporte y distribución. Estas máquinas, como cualquier otra, necesitan que su desempeño sea evaluado continuamente y que se lleven a cabo planes de mantenimiento predictivo, preventivo y correctivo. Una herramienta útil para esta labor, son los mapas de operación; dichos mapas en ocasiones los proporciona el fabricante; sin embargo, estos se generan a las condiciones de presión y temperatura en talleres donde el fabricante hace las pruebas antes de venderlo, además de que el compresor opera con una composición específica de gas natural diferente al que se tiene en el sitio destinado para su instalación. Lo anterior implica que, al trasladarlo a otra región con condiciones de presión y temperatura diferentes a las de diseño, y al operarlo con otra composición de gas natural, el desempeño de la máquina no será el mismo, entonces es necesario actualizar los mapas cada que estos parámetros cambien. Motivados por lo anterior, en este trabajo se propone una metodología para generar los mapas de operación actualizados de los compresores centrífugos modelo 2BCL608/N de la marca Nuovo Pignone, considerando los cambios en la composición del gas natural, y el cambio en la presión y temperatura de succión. Con estos mapas se evalúa el desempeño de los mismos compresores y se hacen recomendaciones de operación según los resultados obtenidos